2013
DOI: 10.14260/jemds/1151
|View full text |Cite
|
Sign up to set email alerts
|

Study of Personal Hygiene, Nutritional and Morbidity Profile of School Children in Rural Area of Khammam District, Andhra Pradesh

Abstract: BACKGROUND: Majority of the health problems of school children can be prevented by promotion of hygiene and sanitation through health education of school children, teachers and parents. OBJECTIVES: 1. To find out the status of personal hygiene among the primary school children. 2. To study the nutritional and morbidity profile of the school students. MATERIALS AND METHODS: A cross sectional study was conducted among primary school students in rural area of Khammam district, A.P. RESULTS: the study included 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
1
3
0
Order By: Relevance
“…2 In another study conducted by Aditya et al, the prevalence of underweight was more in boys (32.3%) when compared to girls (30.6%). 20 Madhavi et al conducted a study and reported that boys (66.7%) were more malnourished than girls (52.5%) which was similar to our study. 11…”
Section: Malnutritionsupporting
confidence: 91%
See 2 more Smart Citations
“…2 In another study conducted by Aditya et al, the prevalence of underweight was more in boys (32.3%) when compared to girls (30.6%). 20 Madhavi et al conducted a study and reported that boys (66.7%) were more malnourished than girls (52.5%) which was similar to our study. 11…”
Section: Malnutritionsupporting
confidence: 91%
“…In this present study prevalence of anaemia was found to be 97.7%, which is very higher and significant than all other studies like Charuhas ). 11,20,[23][24][25][26][27][28] In this present study prevalence of anaemia was found more in girls with 55.8% of girls were anaemic and boys 44.2% are found to be anaemic. In other study by Madhavi similar findings were observed with girls (65.35%) were anaemic than boys (34.65%).…”
Section: Anemiamentioning
confidence: 72%
See 1 more Smart Citation
“…8 In other words, schools provide an opportunity to better educate the children regarding different aspects of health such as nutrition, immunization, hygiene, environment, sanitation, social customs and so on. 7,9 Regular school health check-ups can prevent complications in school children by early detection of childhood illnesses. 10 The school and family are the two major sources from one can develop a strong base for hygienic practices.…”
Section: Introductionmentioning
confidence: 99%